MYC: there is more to it than cancer - Zacarías-Fluck, Mariano F.; Soucek, Laura; Whitfield, Jonathan R. (Frontiers in Cell and Developmental Biology, 2024)
MYC is a pleiotropic transcription factor involved in multiple cellular processes. While its mechanism of action and targets are not completely elucidated, it has a fundamental role in cellular proliferation, differentiation, metabolism, ribogenesis, and bone and vascular development.Over four decades of research and some 10,000 publications linking it to tumorigenesis (by searching PubMed for "MYC oncogene") have led to MYC becoming a most-wanted target for the treatment of cancer, where many of MYC's physiological functions become co-opted for tumour initiation and maintenance. In this context, an abundance of reviews describes strategies for potentially targeting MYC in the oncology field. However, its multiple roles in different aspect of cellular biology suggest that it may also play a role in many additional diseases, and other publications are indeed linking MYC to pathologies beyond cancer.Here, we review these physiological functions and the current literature linking MYC to nononcological diseases. The intense efforts towards developing MYC inhibitors as a cancer therapy will potentially have huge implications for the treatment of other diseases. In addition, with a complementary approach, we discuss some diseases and conditions where MYC appears to play a protective role and hence its increased expression or activation could be therapeutic.